MENINGKATKAN PRESTASI BELAJAR BERHITUNG MELALUI METODE PERMAINAN KARTU BILANGAN - Titis Susilowati (LPPM UNISDA, 2018)
The purpose of this study was to determine the effect of using number card game methods on students' numeracy skills in class II Lopang II Public Elementary School, Kembangbahu District, Lamongan District. This study uses classroom action research method, consisting of two cycles, namely cycle I and cycle II. In the first cycle there were 11 students who experienced individual learning completeness from 18 students (61%) showed that this cycle had not experienced classical completeness. In cycle II there were 17 students who experienced individual learning completeness from 18 students (94%) showed that this cycle had experienced classical completeness. And the increase in the average value of students is 66.67 in the first cycle to 82.50 in the second cycle. From the data above, it can be concluded that there is an effect of using the number card game method on increasing students' ability to count.